Sistematización de la experiencia artístico-pedagógica al estado actual de la creación en la obra teatral “Domitilo y Alicia, el Rey y la Reina de la Rumba” del curso montaje interdisciplinar, teatro, fiesta y carnaval 2022- 2 (2024)
The thesis focuses on the systematization of experiences in the play Domitilo and Alicia, the King and Queen of Rumba, with the aim of carrying out a reflection that understands and deepens the methodological strategies addressed in the processes of collective creation, adaptation and assembly of the play, which were a guide and reference for the construction of a street theater show.